2013
DOI: 10.1038/ncomms3084
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair choice defines a common pathway for recruitment of chromatin regulators

Abstract: DNA double-strand break (DSB) repair is essential for maintenance of genome stability. Recent work has implicated a host of chromatin regulators in the DNA damage response, and although several functional roles have been defined, the mechanisms that control their recruitment to DNA lesions remain unclear. Here, we find that efficient DSB recruitment of the INO80, SWR-C, NuA4, SWI/SNF, and RSC enzymes is inhibited by the non-homologous end joining machinery, and that their recruitment is controlled by early ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 49 publications
4
93
0
Order By: Relevance
“…4) compared with wt mice. Up-regulated miRNA in 3 0 RR-deficient mice have hundreds of ARTICLE predicted targets, including Atm, Ssb1, Ino80, Exo1, Smarcd1, Dclre1b and Atmin, which have been shown to regulate DSB resection and homologous recombination [33][34][35][36][37][38] , and histone modifying enzymes Hdac9 and Esco1. Interestingly, HDAC9 is required for DSB reparation by homologous reparation 39 , and its deletion affects antibody secretion 40 .…”
Section: ′Rr-deficientmentioning
confidence: 99%
“…4) compared with wt mice. Up-regulated miRNA in 3 0 RR-deficient mice have hundreds of ARTICLE predicted targets, including Atm, Ssb1, Ino80, Exo1, Smarcd1, Dclre1b and Atmin, which have been shown to regulate DSB resection and homologous recombination [33][34][35][36][37][38] , and histone modifying enzymes Hdac9 and Esco1. Interestingly, HDAC9 is required for DSB reparation by homologous reparation 39 , and its deletion affects antibody secretion 40 .…”
Section: ′Rr-deficientmentioning
confidence: 99%
“…These results suggest that, although Tel9R and Tel13R-f share overlapping nuclear territories (Agmon et al, 2013), the proximity of homologous sequences is not sufficient for homologous repair to take place efficiently in the presence of latrunculin. The drop in the efficiency of homologous recombination in the presence of latrunculin A remains to be further characterized and could result from several mechanisms that are not mutually exclusive -the established role for actin in the INO80 complex (Agmon et al, 2013;Bennett et al, 2013;Horigome et al, 2014;Kapoor et al, 2013) -or a possible role in facilitating homology search through chromosome jiggling.…”
Section: -Gfp-labeled Cells (Wt) That Had Been Treated With Dmso or 3mentioning
confidence: 99%
“…We found that actin-dependent chromosome movements affect homologous recombination repair efficiency. This repair mechanism requires the recruitment of INO80, SWR-C, NuA4, SWI/SNF and RSC to the DSBs during S phase (Bennett et al, 2013). Interestingly, the INO80, SWR-C and NuA4 complexes contain actin in both yeast and mammals (for review, see Kapoor and Shen, 2014).…”
Section: Functional Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu and colleagues showed that knockdown models of human INO80, or of its binding partner YY1, increased cellular sensitivity toward DNAdamaging agents, and in their study they highlighted the essentiality of both INO80 and YY1 for HR repair (Wu, S. et al, 2007). However, a recent report indicated that H2A phosphorylation is dispensable for recruitment of the chromatin remodelers INO80 and SNF6 (a component of SWI/SNF) to DSB sites in yeast (Bennett et al, 2013), suggesting that the interaction with γ-H2AX may not be essential for directing the accumulation of histone remodelers at DSB damage sites.…”
Section: Introductionmentioning
confidence: 99%